Accuracy of scleral transillumination techniques to identify infant ciliary body for sclerostomy and intravitreal injections. (10th December 2018) - Sharma, Abhishek; Ali, Asim; Henderson, Robert H.; Patel, C. K.; VandenHoven, Cynthia; Lam, Wai‐Ching
Abstract : Importance: There is variation in the literature for sclerotomy and intravitreal injection placement in young children, ranging from 0.5 to 3.0 mm from the limbus. We assess the accuracy of scleral transillumination to identify the ciliary body in infants for safe sclerotomy and intravitreal injections in young children. Background: The study compares the perilimbal "dark band" seen on scleral transillumination (STI) with the ultrasound biomicroscopy (UBM), and compares these measurements with the current guidelines for sclerotomy in infants. Design: Prospective case series in a tertiary paediatric hospital. Participants: Children aged ≤36 months undergoing general anaesthesia for eye procedures. Methods: Scleral transillumination was performed to measure the perilimbal dark band. UBM of the ciliary body region was then performed, and correlated with transillumination findings. Main Outcome Measures: The midpoints of STI and UBM were compared to current cadaver‐based guidelines to assess the safe point for sclerotomy. Results: Twenty children were recruited, 36 STI and 35 UBM measurements were obtained. The posterior edge of the dark band had good correlation with the posterior border of the ciliary body. Transillumination and UBM correlated well for midpoint measurements. The midpoint of the dark band on transillumination was confirmed to be in the ciliary body by UBM in all cases. Conclusions and Relevance: The STI technique is a useful and fast technique to demonstrate the ciliary body. The midpoint of the dark band on STI correlates well with the UBM, and has a potential use for confirming safe‐entry into the posterior segment if using current guidelines. The current cadaver‐based paediatric guidelines safely avoid retinal injury.